Linking Home Care Interventions and Hospitalization Outcomes for Frail and Non-frail Elderly Patients - Monsen, Karen A. (Res Nurs Health, 2011)
Structured clinical data generated using standardized terminologies such as the Omaha System are available for evaluating health care quality and patient outcomes. New intervention management grouping approaches are needed to deal with large, complex clinical intervention data sets. We evaluated 56 intervention groups derived using four data management approaches with a data set of 165,700 interventions from 14 home care agencies to determine which approaches and interventions predicted hospitalizations among frail (n=386) and non-frail (n=1,364) elders. Hospitalization predictors differed for frail and non-frail elders. Low frequencies in some intervention groups were positively associated with hospitalization outcomes, suggesting that there may be a mismatch between the level of care that is needed and the level of care that is provided.